2004
DOI: 10.1152/jn.00855.2003
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Layer V Pyramidal Neurons in the Rat Prefrontal Cortex: Intrinsic Properties and Synaptic Function

Abstract: Layer V pyramidal neurons in the rat medial prefrontal cortex (PFC) were examined with whole cell patch-clamp recording in acute slices from postnatal day 1 (P1) to P36. In the first few days after birth, layer V pyramidal neurons had low resting potentials, high-input resistance, and long membrane time constant. During the next 2 wk, the resting potential shifted by -14 mV, while the input resistance and time constant decreased by 15- and 4-fold, respectively. Between P3 and P21, the surface area of the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
178
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(211 citation statements)
references
References 58 publications
28
178
1
Order By: Relevance
“…Consistent with our findings for Kv-mediated currents, the most dramatic changes in AP parameters occur between weeks 1 and 3, approaching adult values by weeks 3-5 (Lorenzon and Foehring 1993;McCormick and Prince 1987;Zhang 2004). Because of its relatively hyperpolarized activation range and fast kinetics (Foehring and Surmeier 1993;Yuan et al 2005), the maturation of A-type current would be expected to lead to more rapid spike repolarization and narrower spikes.…”
Section: Development Of Excitability and Firing Patternssupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with our findings for Kv-mediated currents, the most dramatic changes in AP parameters occur between weeks 1 and 3, approaching adult values by weeks 3-5 (Lorenzon and Foehring 1993;McCormick and Prince 1987;Zhang 2004). Because of its relatively hyperpolarized activation range and fast kinetics (Foehring and Surmeier 1993;Yuan et al 2005), the maturation of A-type current would be expected to lead to more rapid spike repolarization and narrower spikes.…”
Section: Development Of Excitability and Firing Patternssupporting
confidence: 85%
“…Pyramidal cell resting membrane potential (RMP) becomes more hyperpolarized with postnatal development and input resistance and membrane time constant decrease Beique et al 2004;Christophe et al 2005;Kasper et al 1994aKasper et al , 1994bLorenzon and Foehring 1993;Maravall et al 2004a;McCormick and Prince 1987;Metherate and Aramkis 1999;Oswald and Reyes 2008;Tyzio et al 2003). Repetitive firing behavior also changes with age Christophe et al 2005;Kasper et al 1994aKasper et al , 1994bLorenzon and Foehring 1993;Maravall et al 2004aMaravall et al , 2004bMcCormick and Prince 1987;Metherate and Aramkis 1999;Oswald and Reyes 2008;van Brederode et al 2000;Zhang 2004). In mature pyramidal neurons, voltage-gated K ϩ channels contribute to the filtering and integration of synaptic inputs, as well as shaping firing rates and pattern (Guan et al 2007a;Higgs and Spain 2009;Schwindt et al 1988).…”
mentioning
confidence: 99%
“…In human studies, McKinstry et al (2002) reported that the time course of anisotropy diminishment coincides with the period of "cortical maturation" (Sidman and Rakic, 1982) and attributed the decrease to the growth of dendrites, as well as formation of cell processes and their connections, to the arrival of local circuit neurons and their differentiation, and to the disappearance of the radial glia (Sidman and Rakic, 1973;Kostovic and Rakic, 1990). In rat brains, axonal and dendritic branching in the cortex begins at approximately P1-P7, and the peak of synapse formation occurs at approximately P7-P14, whereas dendrite growth extends to the third week (Miller, 1981;Miller and Peters, 1981;Harris et al, 1992;Wong and Ghosh, 2002;Zhang, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…As described previously by Zhang (2004), slices possessing biocytin-filled cells were carefully removed from the recording chamber and fixed by immersion in 4% paraformaldehyde in 0.1 M PBS overnight at 4°C, followed by two rinses in PBS (0.1 M). The slices were then incubated in 3% H 2 O 2 and 10% methanol in PBS (0.1 M) for 1 h at room temperature to quench endogenous peroxidase activity, which was followed by five 5 min washes in PBS plus 0.1% Triton.…”
Section: Methodsmentioning
confidence: 99%